Prospects of Applying Feed Processing Technologies Based on Industrial Plantation - Simon Petrus Ginting (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2012)
The potency of plantation sectors (palm oil, sugar cane and cacao) as alternative feed resources for ruminants has been acknowledged since 20 – 25 years ago. However, the level of utilization of these feeds in small ruminant production system has been very low and sporadic. The typical chemical and physical characteristics of most of those feedstuffs required some steps of processing in order to improve their nutritional quality and to ease their handling. Small ruminants, like sheep and goats have relatively higher metabolic energy requirement per kg BW and anatomically have lower gut capacity to process lignocelluose materials compared to large ruminants. It is, therefore, these animals nutritionally face more constraints in handling lignocellulose and bulky materials mostly found in industrial by products or crop-residues from plantations. Physical processes (chopping, phyiscal separation, hydrothermal), chemical processes (ammoniation, hydrolyses and oxidative treatments) and bio-conversions (fermentation, ensiling) have been recommended as alternative technologies in maximizing the utilization of those feedstuffs for small ruminant animals. The principal mechanisms of those treatments are: (i) breaking the linkages between structural carbohydrate and lignin so that it could be easily digested by the animal enzyme systems and (ii) preserving the material from being spoilage due to its high moisture content or for feed stocking purposes. Priorities for choosing the most effective processing technology for implementation or adoption is depent largely on the scale of feed production. Ammoniation, chopping, physical separation, ensiling or bio-conversion are several technologies mostly recommended for small scale operation in situ. These alternative technologies should be able to be adopted by small-holders living around the plantation area. The commercial or large scale feed production could be implemented by the plantation industry by giving high priority to the processing technology such as hydrolitic treatment using NaOH, ammoniation, hydrothermal, pelleting, wafering or cubing. The types of products that possibly produced in this large operation scales are (i) concentrate feed, (ii) complete feed or (iii) basal feeds (roughages). The chain of ruminant feed production systems could be developed further by including the feed industry sector into the system. Within this system the plantation industry will have main role to supply the raw materials for the feed industries. As these local raw materials are readily available, the feed industries could further produce various types of balanced feed or rations based on the principles of feeding standard to meet the nutrient requirements of various classes of ruminant animals. Key words: Feedstuffs, plantation, processing, small ruminants